The Markers of Territorial Identity in Melitopol, Ukraine. Issue 2 (June 2022) - Bukrieieva, Iryna; Afanasieva, Lyudmila
This article is about the territorial identity of the inhabitants of Melitopol, Ukraine. It focuses on measuring markers of this identity: emotional attachment (proud of the city; love for the city); knowledge of its historical and cultural heritage; city patriotism and citizenship; the density of social communications; and social trust. It reports on results of a representative sociological study "The Markers of Self-Identification of Melitopol Residents, " which was aimed at identifying identities capable of forming a collective identity for this city. This study revealed that there are effective conditions in the city for the formation of a collective territorial identity, namely: There is affinity with its physical space; a significant portion of residents are interested in city issues, which is the basis for forming groups and associations based on common interests within the local community; and there are dense social communications in the media space of the city. On the other hand, the study also found that the city's historical and cultural heritage are not effective factors of the city's identity. The authors conclude the consolidation of the city's identity needs to takes place around contemporary events and circumstances; hence, there is a need to make the city a more useful social space with infrastructure that meets the contemporary needs and interests of its residents. The study also reveals that in Melitopol, like the whole of Ukrainian society, there is a lack of social trust, largely due to the post Soviet Union distrust of political institutions both at the national and local levels. At the same time, there is considerable interest in the consolidation of various social groups and the formation of social trust.